The world's worst children 3 - Walliams, David; Ross, Tony (London harpercollins children's book, 2023)
Are you prepared to meet the worst children ever? look out it's more badly behaved booys and ghoulish girls
From the number one bestselling author
Science fiction
Keywords: Children's -- Teenage fiction & true stories; Children's -- Teenage personal & social issues; English fictions